Polygala azizsancarii (Polygalaceae), a new species from Mardin Province, SE Turkey - Dönmez, Ali̇ A.; Uğurlu Aydin, Zübeyde (Phytotaxa, 2018)
Polygala azizsancarii Dönmez (Polygalaceae) is herein described and illustrated as a new species from Mardin province in SE Turkey. This new species is similar to P. kurdica and P. supina, but it clearly differs by several morphological characters. Diagnostic characters of this new species are discussed with respect to taxonomy and illustrations. Conservation status of the new species is also assessed according to field observations. An updated identification key is presented for the Turkish species of the genus, which currently includes 18 taxa.